2018
DOI: 10.1111/scd.12298
|View full text |Cite
|
Sign up to set email alerts
|

Integrating community service learning in undergraduate dental education: A controlled trial in a residential facility for people with intellectual disabilities

Abstract: Based on the experiences at Ghent University, the following guidelines were suggested to implement service learning in a dental curriculum that renders both a positive impact on student learning and the local community : (1) integrate community service learning in multiple years in the curriculum; (2) use a stepwise approach from theory to exercises to extramural experiences; (3) create a partnership with a local organization; (4) organize long-term projects and annual follow-up to increase the impact; (5) inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
0
15
0
2
Order By: Relevance
“…Multi-tiered training can be effective for caregivers. Mac Giolla Phadraig, Guerin, & Nunn, 2015 (Ireland) [39]Cluster RCTEvaluate impact of OH train the trainer program on OH status and hygiene of people with ID in community based care homes.76 caregivers (male n = 42, female n = 43) of adults with ID.No statistically significant differences in PlI and the GI between control and intervention. Accuracy of outcome measures may be affected by difficulty of oral examination among people with ID. Phlypo et al, 2018 (Belgium) [40]Pre-post intervention study.Explore effect of a dental student developed OH education program for caregivers in a residential facility for people with IDD.Residents with severe to profound ID (intervention n = 18; control n = 19). Caregivers (intervention n = 12; control n = 22).Change of PlI and GI from pre to post did not significantly differ between intervention and control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-tiered training can be effective for caregivers. Mac Giolla Phadraig, Guerin, & Nunn, 2015 (Ireland) [39]Cluster RCTEvaluate impact of OH train the trainer program on OH status and hygiene of people with ID in community based care homes.76 caregivers (male n = 42, female n = 43) of adults with ID.No statistically significant differences in PlI and the GI between control and intervention. Accuracy of outcome measures may be affected by difficulty of oral examination among people with ID. Phlypo et al, 2018 (Belgium) [40]Pre-post intervention study.Explore effect of a dental student developed OH education program for caregivers in a residential facility for people with IDD.Residents with severe to profound ID (intervention n = 18; control n = 19). Caregivers (intervention n = 12; control n = 22).Change of PlI and GI from pre to post did not significantly differ between intervention and control.…”
Section: Resultsmentioning
confidence: 99%
“…At post-test, there was a significant increase in caregiver knowledge but no significant difference in caregiver self-efficacy between the intervention and control groups. The study by Phlypo et al [40], reported on a dental student developed oral health program where the intervention group were provided with booklets, an information session and advice on appropriate toothbrushes and toothpaste. The only significant difference was in post-test GI between the intervention and the control group.…”
Section: Resultsmentioning
confidence: 99%
“…However, for many of these reports, social determinants of health appeared to be an incidental component of the students’ experience because no training activities were specifically implemented to facilitate students’ learning about SDH. Many of the placements involved outreach and oral health promotion 23–31 and immersion into a community organization 32–35 . Two papers described the collaborative development of educational resources which featured filmed interviews with individuals about their experiences with poverty and the impacts of financial hardship on their oral health and access to care 36,37 …”
Section: Resultsmentioning
confidence: 99%
“…[19] In this study, approximately 40.7% of subjects felt underserved patients are difficult to handle. Similarly, in a study conducted by Phlypo et al .,[20] dental students encountered problems when treating patients with poor oral health literacy, the less they enjoyed treating these patients, the less likely they intended to provide care for them in the future. Ultimately, these challenges could interfere with dental students’ level of comfort when providing care to the underserved.…”
Section: Discussionmentioning
confidence: 99%